Antioxidant, Antidiabetic, and Antibacterial Potentials and Chemical Composition of Salvia officinalis and Mentha suaveolens Grown Wild in Morocco. (15th June 2022) - Al-Mijalli, Samiah Hamad; Assaggaf, Hamza; Qasem, Ahmed; El-Shemi, Adel G.; Abdallah, Emad M.; Mrabti, Hanae Naceiri; Bouyahya, Abdelhakim
Abstract : This work evaluated in vitro antioxidant, antidiabetic, and antibacterial properties of Salvia officinalis ( S . officinalis ) and Mentha suaveolens ( M . suaveolens ) essential oils (EO). The EOs were extracted, and their chemical composition was determined using GC-MS analysis. The in vitro antioxidant, antidiabetic, and antibacterial activities of S . officinalis and M . suaveolens EO were shown to be remarkable. Furthermore, S . officinalis EO demonstrated better antioxidant findings (using DPPH, ABTS, and FRAP test) than M . suaveolens EO (p < 0.5 ). There were no significant differences in the inhibitory effects of the EOs on α -amylase and α -glucosidase activities in the antidiabetic assays. All of the examined bacterial strains (10 different strains), with the exception of P . aeruginosa, demonstrated significant sensitivity to the tested EOs, with M . suaveolens EO exhibiting better activity than S . officinalis EO. Thus, the research indicated that EO from these two medicinal plants has considerable potential for application in the formulation of antibacterial, antioxidant, and antidiabetic pharmaceuticals. However, more research studies are required to interpret the pharmacologic action of the studied EOs and their principal constituents and to confirm their safety.